SARS-CoV-2 seroprevalence among 7950 healthcare workers in the Region of Southern Denmark - Sebastian von Huth (Elsevier, 2021)
Objective: Healthcare workers (HCWs) carry a pronounced risk of acquiring severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The aim of this study was to determine the seroprevalence and potential risk factors of SARS-CoV-2 infection among HCWs in the Region of Southern Denmark after the first pandemic wave in the spring of 2020. Methods: This was an observational study conducted between May and June 2020. SARS-CoV-2 IgG and IgM antibodies were measured in plasma. Participants were asked to complete a questionnaire consisting of demographic information, risk factors, and COVID-19-related symptoms. Results: A total of 7950 HCWs participated. The seroprevalence of SARS-CoV-2 antibodies was 2.1% (95% confidence interval (CI) 1.8–2.4%). Seropositive participants were significantly older (mean age 48.9 years vs 46.7 years in seronegative participants, P = 0.022) and a higher percentage had experienced at least one symptom of COVID-19 (P < 0.001). The seroprevalence was significantly higher among HCWs working on dedicated COVID-19 wards (3.5%; OR 2.02, 95% CI 1.44–2.84). Seroprevalence was significantly related to 11–50 close physical contacts per day outside work (OR 1.54, 95% CI 1.07–2.22). Conclusions: The prevalence of SARS-CoV-2 antibodies was low in HCWs. However, the occupational risk of contracting the infection was found to be higher for those working on dedicated COVID-19 wards. Further, the results imply that attention should be paid to occupational risk factors in planning pandemic preparedness.